Effects of Ultrasound and Microwave-Hot Air Drying on the Drying Kinetics and Physicochemical Properties of Mango Powder - Ahmed, Ahmed Abdirahman; Yildiz, Gokcen (Wiley, 2025)
This study evaluated the effects of ultrasound (ULS) pretreatment (15 and 30 min) combined with different drying methods-hot air drying (HAD), microwave drying (MW), and hybrid microwave-hot air drying (MW-HAD)-on the drying kinetics and physicochemical attributes of mango powder. Results demonstrate that 30 min ULS pretreatment with MW-HAD (200 W + 70 degrees C) significantly enhanced drying efficiency, reducing processing time by 80% (p < 0.05). However, quality outcomes were method-dependent: MW drying at 200 W without pretreatment optimally preserved bioactive compounds, maintaining phenolic content (1431.86 mg/100 g GA dry weight) and antioxidant capacity (23.41 mu mol Trolox/g dry weight). Conversely, HAD at 70 degrees C without pretreatment produced powders with superior physical properties, including higher bulk density (0.35 g/cm3) and improved flow characteristics (CI = 33.35). Functional properties were most enhanced by ULS pretreatment, which increased water solubility index (42.32%) and swelling capacity (48.91 mL/g). These findings provide a framework for industrial process selection: MW drying for nutrient retention, HAD for powder handling, and ULS pretreatment MW-HAD for time-sensitive production. The study emphasizes the importance of method selection based on targeted quality parameters in mango powder processing. Furthermore, future research should focus on optimizing ULS parameters to simultaneously maximize efficiency and quality, facilitating the industrial adoption of this promising technology.
Keywords: hot air drying; mango powder; microwave; pretreatment; ultrasound